Acoustic speech analysis in Alzheimer’s disease: a systematic review and meta-analysis - Saeedi, Saeed; Hetjens, Svetlana; Grimm, M. O. W.; Barsties v. Latoszek, Ben (The journal of prevention of Alzheimer's disease, 2024)
The potential of biomarkers in the detection of Alzheimer’s disease (AD) is prominent. Acoustics may be useful in this context but the evaluation and weighting for specific acoustic parameters on continuous speech is missing. This meta-analysis aimed to explore the significance of acoustic parameters from acoustic speech analysis on continuous speech, as a diagnostic tool for clinical AD.
Online veröffentlicht: 13. August 2024
Gesehen am 05.11.2024